Um fio da meada: Experiência e luta dos trabalhadores têxteis em Fortaleza (1987 - 1991) - Gomes, Francisco Alexandre (2012)
The aspect of this investigation has your focus in experience and fight of textile workers in Fortaleza, with emphasis on workers factory Finobrasa, between the years 1987 and 1991. The main goal is identify the nature of conflicts between workers and company, moreover, understand the context, circumstances and the developments of specific struggles, as the right to unionize and the end of work on Sundays; collective actions of open resistance, as example of the strike on may of 1988 and accession the general strike on 1991. The Construction of history those workers happened from many sources, including narratives of workers of the Finobrasa and unionists, newspapers, informative from employers organizations, documents of Finobrasa, documents of Textile Workers Union of Fortaleza and processes of the judiciary labor. The main inspirations of the study were founds in social work history, as also in both the studies of historians of metier, besides of anthropologists, sociologists and economists. The analysis were centered at the juncture of the policies of industrialization, that subsidized with public funds the manufacturing enterprises in Ceará, when the textile factory in Ceará had a strong growth. In this proclaimed phase of the most productive and competitive in Brazil, of the point of the view of capital, the study examines the conditions of life and work: workers lose their hearing, tuberculosis was “common disease”, and machines “swallowed” employees and the mutilated body worker. When claiming rights, they were fired or they stayed marked in “black lists”, and criminalized your forms of organization. They went to fight. To guarantee and expand the social and political rights; of construction of a trade union movement of base, with strong reference class and more accustomed to collective actions, the textile workers of Fortaleza built strikes, they were justice, they negotiated directly with employers, they closed streets in manifestation; they spun and wove struggle for better conditions of life and work. “The thread of the argument” is soaked of sensibilities, achievements, failures, struggles, outrage, anger, dream and hope, is the organization of this work.